An Empirical Study of R&D Investment Patterns, Effects, and Critical Factors in High-Tech Industries in Taiwan : The Case of the Hsinchu Science-Based Industrial Park (Malaysian Management Journal, 1997)
This research is an empirical analysis of high-tech firms at the Hsinchu Science-based Industrial Park (HSIP) in Taiwan. In this study, three main areas were systematically evaluated: the patterns of R&D intensity along the company's attributes of capital source, industrial category, and age; the relationships between firms' R&D investment and performance; and the critical factors of successful R&D management.